Miejsce badań nad idiolektem w obrębie językoznawstwa - Kozłowska, Anna (Poznańskie Spotkania Językoznawcze, 2015)
The article attempts to portray transformations of the research on the idiolect in Polish linguistic studies of the last two centuries. In this research some distinct tendencies can be observed: inscreasing number of works devoted to different idiolects, widening circle of described individuals, as well as new theoretical approaches to the problem, closely related to main paradigms of contemporary linguistics: above all the concept of the idiolect as an individual communication competence or as a structure containing the individual worldview. The evolution of understanding the idiolect is still involving new phenomena considered as idiolect components into the field of research. Some linguistic currents regard the idiolect as more primal than the common language, which is treated as the overlap of many idiolects. Because of all these the research on idiolects are clearly put forward from margins of linguistics towards its centre. It seems there are new currents and linguistic disciplines that influence discovering the value of the idiolect as an object of linguistics. Focusing on the idiolect results also from tendencies present in other disciplines as well as from the individualistic aspect of the contemporary culture.